Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Perkembangan Identitas Diri Siswa Sekolah Dasar: Penelitian - Ragilia Avriliani; Izdihar Hanifah; Didik Tri Setiyoko (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The formation of self-identity in elementary school students is a crucial developmental process shaped by learning experiences and social interactions. One instructional model believed to support identity development is Project Based Learning (PjBL). This study aims to analyze the literature on the influence of PjBL on the development of elementary students’ self-identity, encompassing cognitive, affective, and social dimensions. The research employed a qualitative method with a literature review approach, drawing from international journals, nationally indexed journals (Sinta), and academic books published within the last 5–10 years. The findings indicate that PjBL enhances critical thinking, conceptual understanding, and problem-solving skills (cognitive); fosters responsibility, independence, and self-confidence (affective); and develops teamwork, leadership, and group identity (social). Challenges in implementing PjBL include time constraints, limited facilities, and teacher preparedness, which can be mitigated through adaptive strategies. The novelty of this study lies in its focus on self-identity development rather than solely academic outcomes. The main contribution of this review is providing a perspective that PjBL serves as a pedagogical strategy to strengthen both personal and social identity among elementary school students from an early age.